Trouble - Schmidt, Gary D. (New York : Clarion Books, 2008)
Fourteen-year-old Henry, wishing to honor his brother Franklin's dying wish, sets out to hike Maine's Mount Katahdin with his best friend and dog, but fate adds another companion--the Cambodian refugee accused of fatally injuring Franklin--and reveals troubles that predate the accident.
Library Media Connection starred.
School Library Journal starred.
Wilson's Junior High School.
Bulletin (Center for Children's books), April 2008.
Horn Book, October 2008.
Kirkus Review, April 2008.
Keywords: Cambodian Americans -- Juvenile fiction; Death -- Juvenile fiction; Dogs -- Juvenile fiction; Families -- Massachusetts -- Juvenile fiction; Prejudices -- Juvenile fiction; Refugees -- Juvenile fiction; Traffic accidents -- Juvenile fiction; Accidents -- Fiction; Cambodian Americans -- Fiction; Death -- Fiction; Dogs -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Refugees -- Fiction; Accidents -- Fiction; Cambodian Americans -- Fiction; Death -- Fiction; Dogs -- Fiction; Family life -- Fiction; Prejudices -- Fiction; Refugees -- Fiction; Katahdin, Mount (Me.) -- Juvenile fiction; Massachusetts -- Juvenile fiction; Katahdin, Mount (Me.) -- Fiction; Massachusetts -- Fiction; Katahdin, Mount (Me.) -- Fiction; Massachusetts -- Fiction